(untitled) (Research, Society and Development, 2021)
Objective: To present excerpts from the History of Pharmacy in the municipality of Belém, Pará, from the 16th century, starting from social, political, economic, sanitary, and educational contexts. Method: This is a Narrative Review presented through synthesis narrative. Results: The History of Pharmacy is presented, highlighting the capital Belém, in the pre-colonial, colonial, imperial, independent, republican period, in the belle époque, in the Getúlio Vargas era and Manoel Barata, after the Estado Novo, in the period of the military regime and in the new republic. Conclusion: The History of Pharmacy in the city of Belém, Pará, is influenced by ideological, political, economic, and social factors. It provides a glimpse into the mythical and exotic past of pharmacies as health establishments, pharmaceutical services, and pharmaceutical care in the health-disease process in the context of the Eastern Amazon.